APPARATUS FOR MANUFACTURING DISPLAY DEVICE AND METHOD FOR MANUFACTURING DISPLAY DEVICE - KIM, Hwan Jin; KANG, Sung Yong (2025)
An apparatus for manufacturing a display device includes an application head which applies an adhesive material to a subject, and a selective curing module which curs a portion of the adhesive material, where the selective curing module cures an edge portion of the adhesive material.